Functional Analysis of the Rabbit Temporomandibular Joint Using Dynamic Biplane Imaging - Henderson, Sarah E. (2014)
The dynamic function of the rabbit temporomandibular joint (TMJ) was analyzed through non-invasive three-dimensional skeletal kinematics, providing essential knowledge for understanding normal joint motion. The objective of this study was to evaluate and determine repeatable measurements of rabbit TMJ kinematics. Maximal distances, as well as paths were traced and analyzed for the incisors and for the condyle-fossa relationship. From one rabbit to another, the rotations and translations of both the incisors and the condyle relative to the fossa contained multiple clear, repeatable patterns. The slope of the superior/inferior incisor distance with respect to the rotation about the transverse axis was repeatable to 0.14 mm/degree and the right/left incisor distance with respect to the rotation about the vertical axis was repeatable to 0.03 mm/degree. The slope of the superior/inferior condylar translation with respect to the rotational movement about the transverse axis showed a consistent relationship to within 0.05 mm/degree. The maximal translations of the incisors and condyles were also consistent within and between rabbits. With an understanding of the normal mechanics of the TMJ, kinematics can be used to compare and understand TMJ injury and degeneration models.